An Analysis of Customer Satisfaction for Hyundai Motor India - Choudhary, Pooja (International Journal of Psychosocial Rehabilitation, 2020)
The paper is based on the relationship between the customer satisfaction and the product/service quality features of the Hyundai Motor India. This company deals in selling of motor cars basically with various brand names such as Hyundai I 10, I 20, Santro, Elantra etc. Its nearest competitors are Tata Motors and General Motors. It falls under Automobile sector which has an annual growth of about 9.2%, with total sales of about 4.02 million units. The aim of this study shall be to take an in-depth analysis about the performance of Hyundai Motor India and to analyse the satisfaction level of customers by the product/service quality provided by the company. We shall be making use of few SPSS tools in order to conclude about the the objectives taken into consideration. A total of 100 questionnaires have been taken as a sample for this study.